Religious polemics and encounters in late antiquity: boundaries, conversions, and persuasion - Nisula, Timo; Laato, Anni Maria; Irizar, Pablo (Studies on the children of Abraham, 2022)
"Religious Polemics and Encounters in Late Antiquity: Boundaries, Conversions, and Persuasion, explores the intricate identity formation and negotiations of early encounters of the Abrahamic religions (Judaism, Christianity, and Islam). It explores the ever-pressing challenges arising from polemical inter-religious encounters by analyzing the dynamics of apologetic debate, the negotiation and formation of boundaries of belonging, and the argumentative thrust for persuasion and conversion, as well as the outcomes of these various encounters, including the articulation of novel ideas. The Late Antique authors studied in the present volume represent a variety of voices from North Africa, passing through Rome, to Palestine. Together, these voices of the past offer invaluable insight to shape the present times, in hope for a better future"--